Bangun Website Company Profile Interakif Menggunakan CMS Wordpress Sebagai Sarana Promosi Digital - Dimas Satrio Nugroho; Farhan Yorah Pane; Nadya Sadini; Khanif Faozi (CV. Multi Kreasi Media, 2025)
Developments in the world of information technology encourage companies to strengthen their digital presence, one of which is with a company profile website. As a provider of nuclear medicine products. PT Akses Multi Jaya needs a website that is more informative, interactive and user-friendly than the previous one. In this practical work, students redesign the company profile website using WordPress CMS. The method applied is the Waterfall model which includes requirements analysis, design, implementation, testing, and release. The system is designed using UML (Unified Modeling Language), namely Use Case Diagram, Activity Diagram, Class Diagram, and Sequence Diagram. The end of this research is a company profile website that is tested using the black box testing method to test the quality of the website quality. The results show that the new company website has a more responsive appearance, makes it easier for users to access information and has more complete features. With this website, it is expected to increase the existence and competitiveness in the digital era.